Strategi Pengelolaan Paket Wisata Inbound oleh Perusahaan Perjalanan Anggota Association of The Indonesian Tours & Trvel Agencies (ASITA) dalam Mengembangkan Pariwisata di Jawa Barat - Khoirul Fajri; Apay Safari (Manajemen dan Pariwisata, 2026)
The purpose of this study is to evaluate the strategies used by the Association of The Indonesian Tours & Travel Agencies (ASITA) West Java DPD and Travel Agencies (BPW) to improve West Java tourism through the management of inbound tour packages. This study aims to identify the factors that influence the management of inbound tour packages in the process of developing West Java tourism in different eras. The identified problem is the ineffective management of Inbound Tours by ASITA member travel agencies during the Covid-19 pandemic. Many travel agencies are still focused on ticket sales and domestic or international tour packages. To evaluate this issue, the study uses the theory of Rejeki and Hantoro (2020:59) through three stages of tour package organization, namely: (a) preparation or creation of tour package products, (b) administration of tour package organization, and (c) tour implementation (tour operation). This research employs a descriptive qualitative method with data collection techniques through observation, interviews, and literature studies supported by Focused Group Discussion (FGD). The results of this study show that the strategies of ASITA member travel agencies are quite good; however, the variety of tour products is still limited, prices are competitive, and promotional efforts are not yet optimal. The main factors are the lack of experienced human resources and government regulations regarding foreign tourist permits after the pandemic. The researcher recommends that the development of inbound tourism should be carried out with more diverse product variations, intensive promotions, and collaboration between the government and tourism stakeholders to attract international tourists and increase foreign exchange earnings.